MEMBANGUN KECERDASAN ANAK MELALUI DONGENG - Rani Astria Silvera Harahap (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Storytelling or reading stories is one way to grow children's intelligence. Along with the development of the era of storytelling, it was considered an ancient way because it was crushed by the sophistication of modern technology, defeated by gadgets and television, which showed programs that did not necessarily have benefits. However, through fairy tales, children are invited to communicate and try to make an idea about solving a problem. In addition, by storytelling children will also be invited to think in a coherent manner, sharpen their verbal skills, develop children's imagination, and many more benefits. From a fairy tale read by both parents and teachers, there will be a lot of new vocabulary, new knowledge, and moral messages conveyed to children.